Stabilization of Li-S batteries with a lean electrolyte: Via ion-exchange trapping of lithium polysulfides using a cationic, polybenzimidazolium binder - Pham, Chuyen Van; Liu, Lili; Britton, Benjamin; Walter, Michael; Holdcroft, Steven; Thiele, Simon (Sustainable Energy & Fuels, 2020)
Implementing Li-S cells using high S loading and lean electrolyte content is considered the only viable way to achieve competitive specific energy for practical applications. However, under these conditions, the cell cycle life and performance are drastically reduced due to the severe polysulfide shuttle effect, electrolyte depletion, and sluggish electrochemical S conversion. Here we demonstrate that a cationic polymer binder can efficiently mitigate the polysulfide shuttle effect. The employed cationic polymer, poly[2,2′-(2,2′′,4,4′′,6,6′′-hexamethyl-p-terphenyl-3,3′′-diyl)-5,5′-bibenzimidazolium iodide] (HMT-PMBI(I-)), possesses abundant benzimidazolium cations which interact with dissolved polysulfide anions when used as an active binder. Simultaneously, density functional theory calculations show that HMT-PMBI+ loosely binds with TFSI- and Li+, allowing HMT-PMBI(I-) to exchange its I- anion with TFSI- from the electrolyte salt to form HMT-PMBI(TFSI) containing loosely bound Li+. This forms a Li+ conducting phase within the cathode, allowing a reduced electrolyte content. Therefore, the novel active binder enables a stable cyclability of >440 cycles for Li-S batteries with relatively high S-loading (3-4 mg cm-2) and a lean electrolyte content of 6 μl mgS-1. As the cells prepared in this work use inexpensive, commercially available materials and a conventional doctor-blade fabrication approach, the results are highly relevant to practical applications.
CRIS-Team Scopus Importer:2020-03-27